Digital for good : raising kids to thrive in an online world - Culatta, Richard E. (Richard Edward), 1978- (Boston, Massachusetts : Harvard Business Review Press, 2021)
"Kids deserve a better digital future. Help them create it. When it comes to raising children in a digital world, every parent feels underprepared and overwhelmed. We worry that our children will become addicted to online games, be victims of cyberbullying, or get lost down the rabbit hole of social media. We tell them time and again what not to do and list dangers to avoid when online. But this is only a piece of the story. Technology can be a powerful tool for learning, for solving humanity's toughest problems, and for bringing us closer together. How can we raise healthy kids who know how to take advantage of the good technology can bring to their lives, while avoiding the bad? It's time to start a new conversation. Digital for Good offers a refreshingly positive framework for preparing kids to be successful in a digital world-one that shifts the focus away from what kids shouldn't do and instead encourages them to use technology proactively and productively. EdTech expert Richard Culatta outlines five qualities every young person should develop in order to become a thriving, contributing member of the digital world: Be balanced: understand when and how much tech use is healthy Stay informed: be an active and discerning consumer of information online Be inclusive: consider multiple viewpoints with respect Be engaged: use tech to improve your relationships and your community Stay alert: be aware of your actions online and create safe spaces for others Parents and children alike will discover the path to becoming effective digital citizens, all while making our online world a better place"--
Introduction. Welcome home(s) -- Our digital dysfunction -- The urgent need for digital citizenship -- Balanced: using technology on our terms -- Informed: becoming savvy consumers of information -- Inclusive: balancing multiple viewpoints with respect -- Engaged: using tech to make our communities better -- Alert: creating safe spaces online -- The other members of the team -- Our digital future.
Includes index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Added to collection customer.56279.3
Keywords: Internet and youth; Internet -- Moral and ethical aspects; Internet -- Social aspects; Technology and youth; Technology -- Moral and ethical aspects; Technology -- Social aspects; elektronické knihy; electronic books